Diplomasi Indonesia sebagai Anggota Tidak Tetap DK PBB 2019-2020 dalam Mempromosikan Program Prison Deradicalization - Arfin Sudirman; Rafidha Dinda Putri (Global Political Studies Journal, 2021)
Terrorism remains as an urgent and important matter to be discussed. It has been realized that a comprehensive strategy is needed to deal with what happened to the terrorist after they’re caught, since there’s a high possibility of radicalism and recruitment of new member might happen inside the prisons. Moreover, along with the increasing concern of foreign terrorist fighters and human rights issues, using merely hard approaches in dealing with terrorism is no longer sufficient, hence, Indonesia proposed a soft approach using deradicalization program. This research attempts to elaborate the details of Indonesia’s diplomacy as UNSC non-permanent member in 2019-2020 in promoting and encouraging the development of a comprehensive strategy to tackle the problems of terrorism more efficiently and effectively. Descriptive analysis with a qualitative approach was used to arrange this research, with supporting information that was gathered through interviews, official documents and repots, also other literature study. The result shows how Indonesia is using this chance to enhance its role in decision-making process on international forum and increasing its influence as a middle power country in the international community. Keywords : Diplomacy, Deradicalization, Indonesia, Terrorism, UNSC